1999
DOI: 10.1152/ajpendo.1999.277.3.e417
|View full text |Cite
|
Sign up to set email alerts
|

Leptin has acute effects on glucose and lipid metabolism in both lean and gold thioglucose-obese mice

Abstract: Leptin is reported to have effects in peripheral tissues that are independent of its central effects on food intake and body weight. In this study, the acute effects of a single dose of recombinant mouse leptin on lipid and glucose metabolism in lean and gold thioglucose-injected obese mice were examined. Changes were measured 2 h after leptin injection. In lean mice, liver and white adipose tissue (WAT) lipogenesis was inhibited. The activity of the pyruvate dehydrogenase complex (PDHCa), the rate-determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
42
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 49 publications
9
42
0
Order By: Relevance
“…The current study demonstrates that leptin effects on liver lipid metabolism can be mediated by hepatic leptin receptors at physiological leptin concentrations, confirming observations from previous studies (14,15,51). Because we were unable to detect ObRb protein or mRNA (data not shown), similar to previous studies (26,52), it is most likely the predominant ObRa that mediates the lipid-lowering effects of leptin.…”
Section: Figsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study demonstrates that leptin effects on liver lipid metabolism can be mediated by hepatic leptin receptors at physiological leptin concentrations, confirming observations from previous studies (14,15,51). Because we were unable to detect ObRb protein or mRNA (data not shown), similar to previous studies (26,52), it is most likely the predominant ObRa that mediates the lipid-lowering effects of leptin.…”
Section: Figsupporting
confidence: 91%
“…Similar effects on lipid metabolism and/or insulin sensitivity are obtained in normal rodents with acute (9,10) or prolonged (11)(12)(13) hyperleptinemia. In the ZDF rat characterized by non-functional leptin receptors and obesity, elevated hepatic lipid levels are reduced by adenovirusmediated expression of functional wild-type leptin receptors in liver (14), whereas administration of leptin to gold-thioglucosetreated mice that lack hypothalamic leptin function decreases hepatic lipogenesis (15). Taken together, these studies demonstrate potent lipid-lowering effects of leptin that are at least partially mediated by direct action of leptin on liver.…”
mentioning
confidence: 72%
“…It could act to modulate insulin secretion and aid normoglycaemia, thereby explaining why leptin administration had no adverse effect on plasma glucose in the present study. Acute and chronic leptin treatment lowers circulating insulin levels in rodents in vivo (Sivitz et al 1997, Bryson et al 1999, although this has not been confirmed in human islets in vitro (Brown et al 2002). Exposure of rat islets to elevated plasma NEFA concentration, which has long-term (inhibitory) and short-term (stimulatory) effects on glucose-stimulated insulin secretion, did increase UCP2 abundance (Lameloise et al 2001).…”
Section: Leptin and Ucp2 In The Neonatal Pancreasmentioning
confidence: 99%
“…Leptin at physiological doses has been shown to inhibit both basal and glucose-stimulated insulin secretion in vitro (Emilsson et al 1997, Roduit & Thorens 1997, and to lower circulating insulin levels in vivo in adult rodents (Sivitz et al 1997, Bryson et al 1999. Levels of rat pancreatic islet UCP2 mRNA are enhanced by recombinant adenoviral-induced leptin expression (Zhou et al 1997) and UCP2 has also been genetically linked to type II diabetes (Fleury et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It crosses the blood-brain barrier and exerts weight-reducing effects including promotion of sugar and fat metabolism, inhibition of food intake and the enhancement of energy consumption [11]. In addition to these effects on the central nervous system, leptin has been reported to exert its influence on a variety of physiological activities including hematopoiesis [12], reproductive function [13,14] and thermoregulation [15].…”
Section: Introductionmentioning
confidence: 99%